Ocular involvement of multicentric malignant B-cell lymphoma in a ewe - Rushton, James O.; Thaller, Denise; Krametter-Froetscher, Reinhild (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2017)
An 8.5-year-old, 98 kg female mountain sheep presented with bilateral exophthalmos with reduced retropulsion of the globes, impairing physiologic eyelid closure, sanguineous ocular discharge, as well as swelling of the eyelids and periocular skin. Bilateral vitreal hemorrhage hindering examination of the fundus was further noticed. Systemic signs included reduced general demeanour, presence of a firm mass in the left half of the mammary gland, multiple masses in the area of the vulva and a mass between the shoulder blades. Complete diagnostic work-up, i. e. complete blood count, blood chemistry and coagulation status, fine needle aspiration of periocular swellings and incisional biopsy of the vulvar masses revealed a diagnosis of malignant B-cell lymphoma. Due to the deterioration in general demeanour and rapid progression of exophthalmos, resulting in bilateral corneal ulceration, despite symptomatic medical treatment, the ewe was humanely euthanized. Gross necropsy and histopathology of select tissue samples confirmed the diagnosis of multicentric malignant B-cell lymphoma. To the authors’ knowledge, this is the first report of multicentric malignant B-cell lymphoma involving the ocular adnexa in sheep.
Keywords: Adnexa; eye; lymphoma; neoplasia; retrobulbar; sheep